The effect of transfer pricing, thin capitalization, deferred tax, and inventory intensity on tax avoidance - Ardiles, M.; Yuliansyah, Yuliansyah; Suhendro, Saring (Journal of Multidisciplinary Academic and Practice Studies, 2024)
Purpose: This study aims to determine the effects of transfer pricing, thin capitalization, deferred tax, and inventory intensity on tax avoidance. Method: This study uses a quantitative approach with a sample of all companies listed on the Indonesia Stock Exchange (BEI) from 2018 to 2022. A purposive sampling technique was used for sample selection, and a sample of 107 companies was selected. This study uses a panel data analysis. The results of the analysis show that thin capitalization and deferred taxes have a negative effect on tax avoidance, while transfer pricing and inventory intensity have no effect on tax avoidance. Results: The findings reveal that transfer pricing and inventory intensity have no significant effects on tax avoidance. Thin capitalization shows a negative and significant effect, suggesting that higher debt usage reduces tax avoidance due to creditor scrutiny and compliance pressure. Deferred tax also negatively affects tax avoidance, indicating that higher deferred tax expenses reflect greater compliance and lower avoidance. The model’s adjusted R² was 7%, implying that most variations in tax avoidance are explained by other unobserved factors. Conclusions: Deferred tax and thin capitalization serve as deterrents to tax avoidance, whereas transfer pricing and inventory intensity are not significant drivers. Limitations: This study relies on publicly available financial reports, limiting the measurement accuracy of hidden tax-avoidance practices. It also covers a period influenced by Covid-19 tax incentives and voluntary disclosure programs, which potentially affect behavior. Contribution: This study extends the literature by integrating inventory intensity into tax avoidance models and providing evidence from Indonesian firms, offering insights for policymakers and regulators to strengthen anti-avoidance measures.